Childfree Dalam Perspektif Maslahah Ammah - Ika Siti Maisyaroh; Abdul Mun'im Saleh; Abid Rohmanu (Journal of Economics, Law, and Humanities, 2024)
In recent times, there is a growing opinion that children can represent both an economic and psychological burden for parents, leading some couples to opt for a childfree lifestyle. However, as children represent the nation’s next generation, preserving offspring is essential and aligns with the fundamental need of hifz al-nasl (protection of lineage). This research aims to provide a broad understanding of the childfree choice, exploring the reasons behind it and analyzing them through the lens of maslahah ‘ammah (public benefit). Conducted as a library research study with a content analysis approach, the findings indicate that childfree remains a relatively new and minority choice in Indonesia. The reasons for choosing childfree are categorized into three main factors. First, economic factors include concerns about financial constraints and potential disruption to economic stability. Second, psychological factors reflect ideals, mental health issues, or past traumas. Third, environmental factors stem from worries about overpopulation and carbon emissions. From the perspective of maslahah ‘ammah, the childfree choice could threaten the nation's interests by decreasing the birth rate and impacting the future generation. Nonetheless, childfree may be permissible in cases of emergency or exceptional circumstances.